Dynamics of Land Use, Land Cover Changes and Their Impacts on Land Surface Temperature Using Satellite Imagery - Temesghen E. Sereke; Tumuzghi Tesfay; Vitaly V. Bratkov; Elsayed S. Mohamed; Dinh T. Quyen (RUDN Journal of Engineering Research)
Population growth and urbanization have resulted in land use/land cover (LULC) changes and affect land surface temperature (LST), which contributes to global warming. The study aimed to detect the LULC changes across Mendefera, Eritrea, from 2002 to 2022, and examine their impacts on LST. Two Landsat-7 ETM and One Landsat OLI_TRI-8 images from 2002, 2012 and 2022 were utilized. A supervised vector machine algorithm was used to classify LULC. Overall accuracy and Kappa coefficient were calculated. Linear regression was performed to show the relationship between Normalized Difference Vegetation Index (NDVI) and LST. The study found remarkable LULC changes in the study area 2002-2022. Built-up and agricultural areas increased by 113.5 and 64.4% respectively, whereas natural vegetation and open areas decreased by 77.6 and 24.8%, respectively. The highest and lowest mean LST were recorded in built-up (35oC) and natural vegetation (29.7oC) areas, respectively. Generally, mean LST decreased by 3.3oC in the study area from 2002 to 2022, and a negative correlation was observed between NDVI and LST. Thus, the study concludes that urbanization causes vegetation degradation, abrupt built-up growth and urban heat islands. The study will help planners and decisions-makers in planning appropriate mechanisms in land use planning and climate change mitigation.